Quickly-cured composite salt grouting material with adjustable curing time

By adding composite nanoporous materials to the acrylate mixture and selecting appropriate curing agents, a fast-curing composite salt grouting material with adjustable curing time is prepared, which solves the problem of reduced mechanical properties and anti-seepage properties of acrylate grouting materials in the prior art under different construction environments, and achieves rapid curing and improved mechanical properties of the materials.

CN119529158APending Publication Date: 2025-02-28SICHUAN TONGSHEN WATERPROOF ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411605520.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing acrylate grouting materials cannot meet diverse needs under different construction environments, resulting in a reduction in their mechanical properties and anti-seepage properties.

Method used

By adding composite nanoporous materials to the acrylate mixture and selecting according to the type of curing agent (medium speed, fast, ultra-fast curing agent), a fast-curing composite salt grouting material with adjustable curing time was prepared.

Benefits of technology

The rapid curing and mechanical properties of composite salt grouting materials have been achieved, and the curing time is adjustable to meet the needs of different construction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129443310000041
    Figure BDA0005129443310000041
  • Figure BDA0005129443310000081
    Figure BDA0005129443310000081
  • Figure BDA0005129443310000101
    Figure BDA0005129443310000101
Patent Text Reader

Abstract

The invention relates to the technical field of building engineering materials, and discloses a rapid curing composite salt grouting material with adjustable curing time. The invention discloses a rapid curing composite salt grouting material with adjustable curing time. The rapid curing composite salt grouting material comprises the following raw materials in parts by mass: 20-30 parts of an acrylate mixture, 3-5 parts of a composite nano-porous material and 1-3 parts of a curing agent. According to the rapid curing composite salt grouting material with the adjustable curing time, provided by the invention, the composite nano porous material is added into the acrylate mixture, so that rapid curing of the composite salt grouting material can be realized, and the mechanical property of the composite salt grouting material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building engineering materials, in particular to a fast-curing composite salt grouting material with adjustable curing time. Background Art

[0002] Acrylate grouting material is a hydrophilic grouting material with acrylate as the main component. It can be polymerized into a solid with gel properties. During the construction process, the acrylate grouting material is injected into the gaps in concrete or rock and soil by applying a certain pressure. The acrylate grouting material can produce a bonding effect with the surrounding concrete and rock and soil, effectively filling the gaps in the concrete and rock and soil; at the same time, the acrylate grouting material will expand to a certain extent during the polymerization process, which can effectively isolate water, thereby achieving the effect of preventing seepage and plugging leakage.

[0003] The construction environment is an important factor affecting the curing of grouting materials. A poor construction environment may lead to a decrease in the mechanical properties and anti-seepage properties of the grouting materials. However, with the continuous upgrading of some engineering requirements, some existing acrylate grouting materials cannot meet the increasingly diverse construction environments. Therefore, in order to meet the needs of different construction environments, developing a fast-curing composite salt grouting material with adjustable curing time has become a technical problem that needs to be urgently solved by technical personnel in this field. Summary of the invention

[0004] The purpose of the invention is to provide a fast-curing composite salt grouting material with adjustable curing time.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A fast-curing composite salt grouting material with adjustable curing time comprises the following raw materials in parts by weight: 20 to 30 parts of an acrylate mixture, 3 to 5 parts of a composite nanoporous material, and 1 to 3 parts of a curing agent.

[0008] Furthermore, the method for preparing the acrylate mixture comprises the following steps: mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, a dispersant and a defoaming agent, and stirring to obtain the acrylate mixture.

[0009] Furthermore, the mass ratio of the water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer is (300-320): (220-240): (170-190): (10-15): (2-5): (2-5).

[0010] Furthermore, the stirring is specifically as follows: controlling the temperature to 60° C., the stirring speed to 40 r / min, and stirring for 40 to 60 min.

[0011] Furthermore, the preparation method of the composite nanoporous material comprises the following steps:

[0012] 1) placing nano-silicon dioxide in a NaOH solution for immersion modification to obtain modified nano-silicon dioxide;

[0013] 2) placing the zeolite in a NaOH solution for impregnation modification to obtain a modified zeolite;

[0014] 3) Mixing the modified nano-silica obtained in step 1) with the modified zeolite obtained in step 2) to obtain the composite nano-porous material.

[0015] Furthermore, in step 1), the concentration of the NaOH solution is 0.1 mol·L -1 .

[0016] Furthermore, in step 1), the mass volume ratio of the nano-silicon dioxide to the NaOH solution is 1 g: 5 mL.

[0017] Furthermore, in step 1), the impregnation modification is specifically: impregnation modification at room temperature for 20 to 40 minutes.

[0018] Furthermore, in step 2), the concentration of the NaOH solution is 0.1 mol·L -1 .

[0019] Furthermore, in step 2), the mass volume ratio of the zeolite to the NaOH solution is 1 g:5 mL.

[0020] Furthermore, in step 2), the impregnation modification is specifically: impregnation modification at 40-50° C. for 50-70 min.

[0021] Furthermore, in step 3), the mass ratio of the modified nano-silica to the modified zeolite is 1:(1-1.2).

[0022] Furthermore, the curing agent can be divided into medium-speed curing agent, fast curing agent and super fast curing agent according to the curing speed.

[0023] The second technical solution of the present invention:

[0024] The preparation method of the above-mentioned fast-curing composite salt grouting material with adjustable curing time comprises the following steps: mixing an acrylate mixture with a composite nanoporous material, allowing the mixture to stand, and then adding a curing agent to obtain the fast-curing composite salt grouting material with adjustable curing time.

[0025] Furthermore, the standing time is 1 to 3 hours.

[0026] The third technical solution of the present invention:

[0027] Application of the above-mentioned fast-curing composite salt grouting material with adjustable curing time in grouting.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The invention provides a fast-curing composite salt grouting material with adjustable curing time. By adding composite nanoporous material into an acrylate mixture, the fast curing of the composite salt grouting material can be achieved and the mechanical properties of the composite salt grouting material can be improved. DETAILED DESCRIPTION

[0030] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0031] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] In the following examples, the room temperature is 25±2°C.

[0036] In the following examples, all the raw materials used are commercially available, as shown in Table 1;

[0037] Table 1 Raw materials and specifications

[0038]

[0039] In the following embodiments, a method for preparing a fast-curing composite salt grouting material with adjustable curing time comprises the following steps:

[0040] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, a dispersant and a defoamer in a mass ratio of (300-320):(220-240):(170-190):(10-15):(2-5):(2-5), controlling the temperature to 60° C., stirring at a speed of 40 r / min, and stirring for 40-60 min to obtain an acrylate mixture;

[0041] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 20 to 40 minutes at room temperature to obtain modified nano-silicon dioxide;

[0042] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 40-50° C. for 50-70 min to obtain a modified zeolite;

[0043] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:(1-1.2) to obtain a composite nanoporous material;

[0044] 5) Weigh each raw material according to the following mass parts:

[0045] 20-30 parts of acrylate mixture, 3-5 parts of composite nanoporous material, 1-3 parts of curing agent;

[0046] Among them, curing agents can be divided into medium-speed curing agents, fast curing agents, and super-fast curing agents according to the curing speed;

[0047] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 1 to 3 hours, the curing agent weighed in step 5) is added to obtain the fast-curing composite salt grouting material with adjustable curing time.

[0048] Example 1

[0049] A medium-speed curing composite salt grouting material

[0050] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 300:220:170:10:2:2, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 40 min to obtain an acrylate mixture;

[0051] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 20 minutes at room temperature to obtain modified nano-silicon dioxide;

[0052] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 40° C. for 50 min to obtain a modified zeolite;

[0053] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1 to obtain a composite nanoporous material;

[0054] 5) Weigh each raw material according to the following mass parts:

[0055] 20 parts of acrylate mixture, 3 parts of composite nanoporous material, 1 part of medium-speed curing agent;

[0056] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 1 hour, the medium-speed curing agent weighed in step 5) is added to obtain the medium-speed curing composite salt grouting material.

[0057] Example 2

[0058] A medium-speed curing composite salt grouting material

[0059] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0060] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 30 minutes at room temperature to obtain modified nano-silicon dioxide;

[0061] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 45°C for 60 min to obtain a modified zeolite;

[0062] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.1 to obtain a composite nanoporous material;

[0063] 5) Weigh each raw material according to the following mass parts:

[0064] 25 parts of acrylate mixture, 4 parts of composite nanoporous material, 2 parts of medium-speed curing agent;

[0065] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 2 hours, the medium-speed curing agent weighed in step 5) is added to obtain the medium-speed curing composite salt grouting material.

[0066] Example 3

[0067] A medium-speed curing composite salt grouting material

[0068] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 320:240:190:15:5:5, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 60 min to obtain an acrylate mixture;

[0069] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed for modification for 40 minutes at room temperature to obtain modified nano-silicon dioxide;

[0070] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed at 50° C. for 70 min to obtain a modified zeolite;

[0071] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.2 to obtain a composite nanoporous material;

[0072] 5) Weigh each raw material according to the following mass parts:

[0073] 30 parts of acrylate mixture, 5 parts of composite nanoporous material, 3 parts of medium-speed curing agent;

[0074] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 3 hours, the medium-speed curing agent weighed in step 5) is added to obtain the medium-speed curing composite salt grouting material.

[0075] Comparative Example 1

[0076] A composite salt grouting material

[0077] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0078] 2) Weigh each raw material according to the following mass parts:

[0079] 25 parts of acrylate mixture, 2 parts of medium-speed curing agent;

[0080] 6) The acrylate mixture weighed in step 5) is mixed with a medium-speed curing agent to obtain the composite salt grouting material.

[0081] The performance of the medium-speed curing composite salt grouting materials prepared in Examples 1 to 3 and the composite salt grouting material prepared in Comparative Example 1 was tested with reference to JC / T 2037-2010 "Composite Salt Grouting Materials". The performance test results are shown in Table 2.

[0082] Table 2 Performance test results

[0083]

[0084] It can be seen from the data in Table 2 that the fast-curing composite salt grouting material with adjustable curing time provided by the present invention uses a medium-speed curing agent as a curing agent, which can achieve medium-speed curing of the acrylate grouting material, and the curing time can reach 21 minutes; moreover, compared with Comparative Example 1 in which no composite nanoporous material is added, the curing time and mechanical properties of the composite salt grouting materials prepared in Examples 1 to 3 are significantly improved.

[0085] Example 4

[0086] A fast-curing composite salt grouting material

[0087] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 300:220:170:10:2:2, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 40 min to obtain an acrylate mixture;

[0088] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 20 minutes at room temperature to obtain modified nano-silicon dioxide;

[0089] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 40° C. for 50 min to obtain a modified zeolite;

[0090] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1 to obtain a composite nanoporous material;

[0091] 5) Weigh each raw material according to the following mass parts:

[0092] 20 parts of acrylate mixture, 3 parts of composite nanoporous material, 1 part of fast curing agent;

[0093] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 1 hour, the fast curing agent weighed in step 5) is added to obtain the fast curing composite salt grouting material.

[0094] Example 5

[0095] A fast-curing composite salt grouting material

[0096] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0097] 2) According to the nano-silicon dioxide and 0.1 mol·L -1The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 30 minutes at room temperature to obtain modified nano-silicon dioxide;

[0098] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 45°C for 60 min to obtain a modified zeolite;

[0099] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.1 to obtain a composite nanoporous material;

[0100] 5) Weigh each raw material according to the following mass parts:

[0101] 25 parts of acrylate mixture, 4 parts of composite nanoporous material, and 2 parts of fast curing agent;

[0102] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 2 hours, the fast curing agent weighed in step 5) is added to obtain the fast curing composite salt grouting material.

[0103] Example 6

[0104] A fast-curing composite salt grouting material

[0105] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 320:240:190:15:5:5, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 60 min to obtain an acrylate mixture;

[0106] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed for modification for 40 minutes at room temperature to obtain modified nano-silicon dioxide;

[0107] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed at 50° C. for 70 min to obtain a modified zeolite;

[0108] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.2 to obtain a composite nanoporous material;

[0109] 5) Weigh each raw material according to the following mass parts:

[0110] 30 parts of acrylate mixture, 5 parts of composite nanoporous material, and 3 parts of fast curing agent;

[0111] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 3 hours, the fast curing agent weighed in step 5) is added to obtain the fast curing composite salt grouting material.

[0112] Comparative Example 2

[0113] A composite salt grouting material

[0114] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0115] 2) Weigh each raw material according to the following mass parts:

[0116] 25 parts of acrylate mixture, 2 parts of fast curing agent;

[0117] 6) The acrylate mixture weighed in step 5) is mixed with a rapid curing agent to obtain the composite salt grouting material.

[0118] The performance of the fast-curing composite salt grouting materials prepared in Examples 4 to 6 and the composite salt grouting material prepared in Comparative Example 2 was tested with reference to JC / T 2037-2010 "Composite Salt Grouting Materials". The performance test results are shown in Table 3.

[0119] Table 3 Performance test results

[0120]

[0121]

[0122] It can be seen from the data in Table 3 that the fast-curing composite salt grouting material with adjustable curing time provided by the present invention uses a fast curing agent as a curing agent, which can achieve rapid curing of the acrylate grouting material, and the curing time can reach 13 minutes; moreover, compared with Comparative Example 2 in which no composite nanoporous material is added, the curing time and mechanical properties of the composite salt grouting materials prepared in Examples 4 to 6 are significantly improved.

[0123] Example 7

[0124] A super fast curing composite salt grouting material

[0125] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 300:220:170:10:2:2, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 40 min to obtain an acrylate mixture;

[0126] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 20 minutes at room temperature to obtain modified nano-silicon dioxide;

[0127] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 40° C. for 50 min to obtain a modified zeolite;

[0128] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1 to obtain a composite nanoporous material;

[0129] 5) Weigh each raw material according to the following mass parts:

[0130] 20 parts of acrylate mixture, 3 parts of composite nanoporous material, 1 part of ultra-fast curing agent;

[0131] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 1 hour, the ultra-fast curing agent weighed in step 5) is added to obtain the ultra-fast curing composite salt grouting material.

[0132] Example 8

[0133] A super fast curing composite salt grouting material

[0134] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0135] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed and modified for 30 minutes at room temperature to obtain modified nano-silicon dioxide;

[0136] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed and modified at 45°C for 60 min to obtain a modified zeolite;

[0137] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.1 to obtain a composite nanoporous material;

[0138] 5) Weigh each raw material according to the following mass parts:

[0139] 25 parts of acrylate mixture, 4 parts of composite nanoporous material, 2 parts of ultra-fast curing agent;

[0140] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 2 hours, the ultra-fast curing agent weighed in step 5) is added to obtain the ultra-fast curing composite salt grouting material.

[0141] Example 9

[0142] A super fast curing composite salt grouting material

[0143] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 320:240:190:15:5:5, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 60 min to obtain an acrylate mixture;

[0144] 2) According to the nano-silicon dioxide and 0.1 mol·L -1 The mass volume ratio of the NaOH solution is 1g:5mL, the nano-silicon dioxide is placed in the NaOH solution, and immersed for modification for 40 minutes at room temperature to obtain modified nano-silicon dioxide;

[0145] 3) According to zeolite and 0.1mol·L -1 The mass volume ratio of the NaOH solution is 1 g: 5 mL, and the zeolite is placed in the NaOH solution and immersed at 50° C. for 70 min to obtain a modified zeolite;

[0146] 4) mixing the modified nano-silica obtained in step 2) with the modified zeolite obtained in step 3) at a mass ratio of modified nano-silica to modified zeolite of 1:1.2 to obtain a composite nanoporous material;

[0147] 5) Weigh each raw material according to the following mass parts:

[0148] 30 parts of acrylate mixture, 5 parts of composite nanoporous material, 3 parts of ultra-fast curing agent;

[0149] 6) The acrylate mixture weighed in step 5) is mixed with the composite nanoporous material, and after standing for 3 hours, the ultra-fast curing agent weighed in step 5) is added to obtain the ultra-fast curing composite salt grouting material.

[0150] Comparative Example 3

[0151] A composite salt grouting material

[0152] 1) mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer in a mass ratio of 310:230:180:12:3:3, controlling the temperature at 60° C., stirring at a speed of 40 r / min, and stirring for 50 min to obtain an acrylate mixture;

[0153] 2) Weigh each raw material according to the following mass parts:

[0154] 25 parts of acrylate mixture, 2 parts of super fast curing agent;

[0155] 6) mixing the acrylate mixture weighed in step 5) with an ultra-fast curing agent to obtain the composite salt grouting material.

[0156] The performance of the ultra-fast curing composite salt grouting materials prepared in Examples 7 to 9 and the composite salt grouting materials prepared in Comparative Example 3 was tested with reference to JC / T 2037-2010 "Composite Salt Grouting Materials". The performance test results are shown in Table 4.

[0157] Table 4 Performance test results

[0158]

[0159] It can be seen from the data in Table 4 that the fast-curing composite salt grouting material with adjustable curing time provided by the present invention uses an ultra-fast curing agent as a curing agent, which can achieve ultra-fast curing of acrylate grouting material, and the curing time can reach 4 minutes; moreover, compared with Comparative Example 3 in which no composite nanoporous material is added, the curing time and mechanical properties of the composite salt grouting materials prepared in Examples 7 to 9 are significantly improved.

[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A fast-curing composite salt grouting material with adjustable curing time, characterized in that: The invention comprises the following raw materials in parts by weight: 20 to 30 parts of acrylate mixture, 3 to 5 parts of composite nano porous material and 1 to 3 parts of curing agent.

2. The fast-curing composite salt grouting material with adjustable curing time according to claim 1, characterized in that: The method for preparing the acrylate mixture comprises the following steps: mixing water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, a dispersant and a defoamer, and stirring to obtain the acrylate mixture.

3. The fast-curing composite salt grouting material with adjustable curing time according to claim 2, characterized in that: The mass ratio of water, heavy calcium carbonate, acrylic acid, N-hydroxyethyl acrylamide, dispersant and defoamer is (300-320): (220-240): (170-190): (10-15): (2-5): (2-5); the stirring is specifically as follows: the temperature is controlled at 60° C., the stirring speed is 40 r / min, and the stirring is performed for 40 to 60 minutes.

4. The fast-curing composite salt grouting material with adjustable curing time according to claim 1, characterized in that: The preparation method of the composite nanoporous material comprises the following steps: 1) placing nano-silicon dioxide in a NaOH solution for immersion modification to obtain modified nano-silicon dioxide; 2) placing the zeolite in a NaOH solution for impregnation modification to obtain a modified zeolite; 3) Mixing the modified nano-silica obtained in step 1) with the modified zeolite obtained in step 2) to obtain the composite nano-porous material.

5. The fast-curing composite salt grouting material with adjustable curing time according to claim 4, characterized in that: In step 1), the concentration of the NaOH solution is 0.1 mol·L -1 ; The mass volume ratio of the nano-silicon dioxide to the NaOH solution is 1g: 5mL; the impregnation modification is specifically: impregnation modification at room temperature for 20 to 40 minutes; in step 2), the concentration of the NaOH solution is 0.1mol·L -1 ; The mass volume ratio of the zeolite to the NaOH solution is 1g:5mL; the impregnation modification is specifically: impregnation modification at 40-50°C for 50-70min; in step 3), the mass ratio of the modified nano-silica to the modified zeolite is 1:(1-1.2).

6. The fast-curing composite salt grouting material with adjustable curing time according to claim 1, characterized in that: The curing agent can be divided into medium-speed curing agent, fast curing agent and super fast curing agent according to the curing speed.

7. A method for preparing a fast-curing composite salt grouting material with adjustable curing time as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: The acrylate mixture is mixed with the composite nanoporous material, left to stand, and then a curing agent is added to obtain the fast-curing composite salt grouting material with adjustable curing time.

8. The preparation method according to claim 7, characterized in that: The standing time is 1 to 3 hours.

9. Use of the fast-curing composite salt grouting material with adjustable curing time as claimed in any one of claims 1 to 6 in grouting.